Cognitive Enhancement, Cheating, and Accomplishment - Goodman, Rob (Kennedy Institute of Ethics journal, 2010)
An ethics of enhancement should not rest on blanket judgments; it should ask us to distinguish between the kinds of activities we want to enhance. Both students and academics have turned to cognition-enhancing drugs in significant numbers—but is their enhancement a form of cheating? The answer should hinge on whether the activity subject to enhancement is zero-sum or non-zero-sum, and whether one is more concerned with excellence in process or excellence in outcome. Cognitive enhancement should be especially tolerated when the activities at stake are non-zero-sum and when the importance of process is outweighed by the importance of outcome. The use of cognition-enhancing drugs does not unnaturally cheapen accomplishments achieved under their influence; instead, cognitive enhancement is in line with well-established conceptions of collaborative authorship, which shift the locus of praise and blame from individual creators to the ultimate products of their efforts.